PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PEMBIBITAN KELAPA SAWIT (Effect of Planting Media Composition On Palm Oil (Elaeis guineensis Jacq) In Pre Nursery) - K.D.,, Sari,; Syahrudin,, Syahrudin,; H., Panupesi, (Universitas Palangka Raya, 2015)
ABSTRACKThe purpose of the research to study the effect of growing media composition on plant growth palmoil in pre nursery. The design used was completely randomized design (CRD) with one factor, namelythe composition of the planting medium with a mixture of fertilizer Petroganik (M) with 6 treatments,namely : M1 (3 kg of alluvial + 1 kg of manure + 1 kg of sandy soil), M2 (3 kg of peat soil + 1 kg ofmanure + 1 kg of sandy soil), M3 (3 kg of alluvial + 1 kg of manure + 1 kg of sandy soil + 0.25 kg oforganic fertilizer), M4 (3 kg of peat soil + 1 kg of manure + 1 kg of sandy soil + 0.25 kg of organicfertilizer), M5 (3 kg of alluvial + 1 kg of manure + 1 kg of sandy soil + 0.50 kg of organic fertilizer)and M6 (3 kg of peat soil + 1 kg of manure + 1 kg of sandy soil + 0.50 kg of organic fertilizer). Thevariables measured were plant height, number of leaf midrib, leaf area, fresh weight and dry weight ofthe total oil palm seedlings. The results showed that the composition of the planting medium with amixture of fertilizer Petroganik significant effect on all variables palm seedling growth (plant height,number of leaf midrib, leaf area, fresh weight and dry weight of the total) in pre nursery. Thecomposition of the planting media of 3 kg alluvial + 1 kg of manure + 1 kg of sandy soil + 0.25 kgorganic fertilizer had a significant effect onthe growth of oil palm seedlings in the pre ursery.